Financial integration in emerging Europe: An enviable development opportunity with tail risks - Aleksandra Iwulska; Naotaka Sugawara; Juan Zalduendo (Center for Social and Economic Research (CASE), 2012)
This paper draws on the experience of emerging Europe and argues that foreign capital is an enviable development opportunity with tail risks. Financial integration and foreign savings supported growth in the EU12 and EU candidate countries. We argue that this was possible because of EU membership (actual or potential) and its role as an anchor for expectations. In contrast, the eastern partnership states did not benefit from the foreign savings-growth link. But financial integration also led to a buildup of vulnerabilities and now exposes emerging Europe to prolonged uncertainty and financial deleveraging due to eurozone developments. Nonetheless, we believe that external imbalances should not be eradicated-nor should emerging Europe pursue a policy of self-insurance. Instead, what we refer to as an acyclical fiscal policy stance could serve to counterbalance private sector behavior. Going forward, a more proactive macroprudential policy will also be needed to limit financial system vulnerabilities when external imbalances are large.
Keywords: E58; F36; F41; G28; 330; Financial integration; Emerging Europe; Capital inflows; Growth; Macroprudential policies; Internationaler Finanzmarkt; Marktintegration; Kapitalmobilität; Wirtschaftswachstum; Finanzmarktregulierung; Europa